Intrauterine administration of peripheral blood mononuclear cells helps manage recurrent implantation failure by normalizing dysregulated gene expression including estrogen-responsive genes in mice - Yoshimi Kitawaki; Akihito Horie; Asami Ikeda; Shimpei Shitanaka; Akihiro Yanai; Tsutomu Ohara; Baku Nakakita; Yusuke Sagae; Asuka Okunomiya; Hirohiko Tani; Masaki Mandai (Cell Communication and Signaling)
Abstract Background Intrauterine peripheral blood mononuclear cell (PBMC) therapy for recurrent implantation failure (RIF) has been reported to improve embryo implantation by acting on the endometrium. However, the exact mode of action of PBMC on the endometrium of patients with RIF remains unclear. In addition, the differences in the therapeutic effects of PBMC therapy with and without human chorionic gonadotropin (hCG) are unknown. Therefore, in this study, we investigated the changes in the endometrium during the implantation phase induced by PBMC administration and the differences in the efficacy of this therapy with and without hCG using a mouse model of implantation failure (IF). Methods IF model was established by the subcutaneous administration of low-dose RU486. Pregnant mice were randomly divided into five groups: control, IF, culture medium, PBMC, and PBMC-hCG (the latter three groups were IF model mice with intrauterine administration). The pregnancy rate and the number and size of implantation sites were recorded during early pregnancy (day 7.5). Uteri from the preimplantation phase (evening of day 3.5) were collected and analyzed using RNA-sequencing (RNA-seq). Results The pregnancy rate, the number of implantation sites, and the number of normal-sized implantation sites were significantly decreased in the IF model and were improved in the medium, PBMC, and PBMC-hCG groups. RNA-seq data showed that PBMC treatment normalized the expression of the majority of dysregulated genes in the endometrium during the preimplantation phase in the IF model, especially the overexpression of estrogen-activated genes. In addition, PBMC treatment increased the expression of local glucocorticoid receptors and suppressed the expression of inflammation-related genes, whereas no significant changes in blood estradiol and glucocorticoid levels were observed. These changes were more pronounced in the PBMC-hCG group and were consistent with the pregnancy outcomes. Conclusions Intrauterine administration of PBMC before embryo implantation promoted embryo implantation in the IF mouse model, and hCG enhanced pregnancy outcomes. PBMC modulated steroid receptor expression and suppressed inflammation and excessive estrogen action.